Effects of glucose and advanced glycation end products on oxidative stress in MIN6 cells - Ge, Q-M.; Dong, Y.; Su, Q. (Cellular and Molecular Biology, 2010)
To explore the mechanism of oxidative stress induced by glucose and advanced glycation end products (AGEs) in MIN6 cells. The MIN6 cells were exposed to various concentrations of glucose or AGEs for some time, MTT assay was used to evaluate the cell viability, reactive oxygen species (ROS) was monitored using intracellular ROS capture Dihydroethidium (DHE) and dihydrorhodamine123 (DHR123). The signal was quantified using flow cytometry by measuring the mean fluorescent intensity (MFI). The NADPH oxidase activity was measured by chemiluminescence with lucigenin. Treatment of high glucose or AGEs decreased cell viability in a dose- and time- dependent fashion. Exposure of MIN6 cells to high glucose or AGEs significantly increased intracellular ROS production in a concentration- and time- dependent manner. In parallel with the results of ROS production, the NADPH oxidase in MIN6 cells was activated due to increased glucose or AGEs concentration. High glucose and AGEs stimulated ROS production via the activation of NADPH oxidase. The oxidative stress may consequently impair pancreatic Î²-cell function and contribute to diabetes mellitus as a result.